(untitled) - Carey, Francis A. (Boston, 2011)
Textbook writ-ing was completely new to my experience, but I have been fortunate to have the support of many talented individuals. I have worked most closely with Jodi Rhomberg, Developmen-tal Editor II, who made my entry into this project as smooth as possible and was extremely patient in dealing with a new author.
Keywords: Chemistry,organic